The Insurability of Third-Party Liability Risks Arising from the Use of Civilian Uncrewed Aircraft Systems (UAS) in the UK - Georgios Leloudas (Insurability of Emerging Risks. Law, Theory and Practice, 2025)
The book chapter discusses the liability and insurance challenges of operating UAS in the UK and whether any changes to the liability and insurance system are required to facilitate their use.